Effects of controlled supramaximal high-intensity interval training on muscle capacities and physical functions for older adults: analysis of secondary outcomes from the Umeå HIT study : a randomised controlled trial - Frykholm, Erik; Hedlund, Mattias; Becker, Clemens; Holmberg, Henrik; Johansson, Bengt; Klenk, Jochen; Lindelöf, Nina; Lindemann, Ulrich; Simonsson, Emma; Boraxbekk, Carl-Johan; Rosendahl, Erik (Age & ageing, 2024)
This study investigated the effectiveness of supramaximal high-intensity interval training (supramaximal HIT) on muscle capacities and physical function compared to moderate-intensity training (MIT) for older adults.Sixty-eight older adults (66-79 years, 56% women), not engaged in regular exercise, were randomised to 3 months of twice-weekly supramaximal HIT (20 minutes including 10 × 6-second intervals) or MIT (40 minutes including 3 × 8-minute intervals). Both groups performed the training on stationary bicycles in a group setting. Target intensity was watt-controlled, with standardised cadence and individualised resistance. Outcomes analysed with linear-mixed models included leg power (Nottingham Power Rig), hand grip strength (Jamar dynamometer), static and dynamic balance (One leg stance, 30-second step test), chair stand (30-second chair stand), and anaerobic cycling performance (modified Borg Cycle Strength Test).Baseline values were (supramaximal HIT/MIT, mean ± SD) leg power 198 ± 60/189 ± 53 W, hand grip strength 4.2 ± 1.0/4.3 ± 1.1 N/kg, static balance 64 ± 41/62 ± 41 s, dynamic balance 39 ± 7/38 ± 5 steps, chair stands 22 ± 6/22 ± 6 and anaerobic cycling performance 224 ± 60/217 ± 55 W. At 3-month follow-up, a between-group difference in favour of supramaximal HIT [95% CI] was observed in anaerobic cycling performance of 19[3;35] W. Within-group mean changes for supramaximal HIT/MIT were for leg power 8.4[0.9;15.8]/6.0[−1.3;13.3] W, hand grip strength 0.14[0.00;0.27]/0.13[−0.01;0.26] N/kg, static balance 11[3;20]/10[1;18] s, dynamic balance 1.6[0.3;2.8]/2.3[1.1;3.6] steps, 2.1[1.1;3.1]/1.4[0.4;2.3] chair stands and anaerobic cycling performance 31.3[19.6;43.0]/12.0[0.4;23.5] W.Supramaximal HIT showed superior effect on anaerobic cycling performance when compared to MIT. Additionally, the results indicate that supramaximal HIT is comparably beneficial as MIT in terms of effects on muscle capacity and physical function for older adults.
Gesehen am 12.05.2025